Assessment 20% oral dextrose induced analgesia during screening for retinopathy of prematurity - Chaithanya Singh; Anupama Bappal; H K Mithun (Journal of Clinical Ophthalmology and Research, 2022)
Aim: The aim of this study was to assess the relief from pain afforded by orally administered 20% dextrose as an analgesic for the purpose of retinopathy of prematurity (ROP) screening. Setting and Study Design: This was an observational case–control subject study design. Materials and Methods: This study was performed over a period of 19 months during the first ROP screening. The readings of clinical and behavioral parameters of preterm babies were taken at baseline and monitored continuously during the screening procedure. The right eye was examined before administration of oral dextrose (WOD) and the left eye was examined after administration of dextrose orally (WD). Babies were given 2 ml of 20% dextrose orally with syringe. ROP screening was performed under topical anesthesia with binocular indirect ophthalmoscope. Pain score was calculated by premature infant pain profile scoring system. Results: One hundred and two babies participated in this study, of which 33 (32.35%) babies had a gestational age ≤32 weeks. Statistical analysis done using Wilcoxon signed-rank test showed significant P values for pain score (P < 0.001), heart rate (P < 0.05), oxygen saturation (P < 0.05), and behavioral parameters (P < 0.001) for WOD and WD. Pain score, WOD, and WD in babies ≤32 and >32 weeks were also significant (P < 0.001) for pain score, heart rate (<0.05), and behavioral parameters except for oxygen saturation (P > 0.05) (Mann–Whitney U test). Conclusions: Oral dextrose has a significant role in reducing pain, during ROP screening, but does not alleviate pain completely. The within-subject study design ensured close to identical baseline parameters, thereby providing better internal reliability of the study.